Semi-automated selection of DNA aptamers using magnetic particle handling. (September 2007) - Wochner, Aniela; Cech, Birgit; Menger, Marcus; Erdmann, Volker A.; Glökler, Jörn
We have developed a semi-automatic selection procedure for DNA aptamers. Employing a robotic workstation for magnetic particle handling, this method allows for a fast, reproducible, and parallelized selection of DNA aptamers. The selection protocol is designed to provide high flexibility and versatility in terms of choice of buffers and reagents, as well as stringency of selection. Using this procedure, we have successfully isolated ligand-specific, high-affinity DNA aptamers.